2001
DOI: 10.1097/00001756-200104170-00017
|View full text |Cite
|
Sign up to set email alerts
|

Insulin inhibits voltage-dependent calcium influx into rod photoreceptors

Abstract: Insulin inhibits the ERG b-wave and modulates L-type calcium currents (I Ca ) in various preparations. We therefore examined insulin's effects on I Ca and depolarization-evoked [Ca 2+ ] i increases in rod photoreceptors. Insulin inhibited I Ca and caused a dose-dependent reduction in the depolarizationevoked Ca 2+ influx with an EC 50 of 2.1 nM. Tyrosine kinase inhibitors, lavendustin A (100 nM) and genistein (10 μM), prevented insulin from reducing the depolarization-evoked Ca 2+ increase in rods. Their less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The amplitude and voltage dependence of photoreceptor I Ca also are affected by a large number of extrinsic neuromodulators, including dopamine , somatostatin (Akopian et al, 2000), cannabinoids (Straiker and Sullivan, 2003;Fan and Yazulla, 2003), adenosine , nitric oxide (Kurenny et al, 1994), insulin (Stella et al, 2001), polyunsaturated fats (Vellani et al, 2000) and various ions. The list of substances that can modulate photoreceptor I Ca is probably not yet complete.…”
Section: Intrinsic Mechanisms That Regulate I Camentioning
confidence: 99%
See 2 more Smart Citations
“…The amplitude and voltage dependence of photoreceptor I Ca also are affected by a large number of extrinsic neuromodulators, including dopamine , somatostatin (Akopian et al, 2000), cannabinoids (Straiker and Sullivan, 2003;Fan and Yazulla, 2003), adenosine , nitric oxide (Kurenny et al, 1994), insulin (Stella et al, 2001), polyunsaturated fats (Vellani et al, 2000) and various ions. The list of substances that can modulate photoreceptor I Ca is probably not yet complete.…”
Section: Intrinsic Mechanisms That Regulate I Camentioning
confidence: 99%
“…I Ca in rods and cones can be regulated by cAMP-dependent protein kinase . Tyrosine kinase inhibitors also alter rod I Ca , suggesting that tyrosine phosphorylation might regulate channel activity (Stella et al, 2001). The ineffectiveness of cGMP analogs (Kurenny et al, 1994) argues against modulation by a cGMP-dependent protein kinase.…”
Section: Intrinsic Mechanisms That Regulate I Camentioning
confidence: 99%
See 1 more Smart Citation
“…Use-dependent feedback mechanisms include voltage-and calcium-dependent inhibition of I Ca [140][141][142][143], inhibition of cone I Ca by the pre-synaptic actions of glutamate on group III mGluRs [208], inhibition of cone I Ca by vesicular protons [208,209], inhibition of I Ca by vesicular zinc [116,210,211], inhibitory effects of adenosine which can be derived from vesicular ATP [212][213][214], inhibition of rod I Ca due to chloride efflux mediated by pre-synaptic glutamate transporters [215], inhibition of rod I Ca due to chloride efflux through calcium-activated chloride channels [138], and enhancement of rod I Ca due to K+ efflux through calcium-activated potassium channels [19]. Various neurotransmitters and neuromodulators also regulate rod and cone I Ca , including nitric oxide [216,217], dopamine [132], cannabinoids [218][219][220], somatostatin [221], insulin [222], retinoids, and polyunsaturated fats [223]. Feedback from horizontal cells onto cones [224] also modulates I Ca [225].…”
Section: Synaptic Depression and Vesicle Replenishmentmentioning
confidence: 99%
“…Stella et al (128) have recently shown that insulin also inhibits influx of Ca 2+ into ISs of rods via the insulin receptor-mediated activation of tyrosine kinases.…”
Section: Insulin Both Inner and Outer Segments Of Photoreceptors Exprmentioning
confidence: 99%